Effect of six weeks of CrossFit training on blood lipid profile and atherogenic index of plasma in young healthy men: A pilot study - Domaszewski Przemysław; Konieczny Mariusz; Skorupska Elżbieta; Ozner Dariusz; Sadowska-Krępa Ewa (Sciendo, 2024)
Study aim: The aim of our study was to determine whether six weeks of CrossFit training, a popular form of high-intensity training, improves the atherogenic index of plasma and blood lipid profile indicators in young healthy men.